Analisis Pelaksanaan Pembangunan TPA Kabupaten Banyumas Akibat Kelongsoran dan Perubahan Desain Perencanaan - Agus Bambang Siswanto; Mukhamad Afif Salim; Hari Setijo Pudjihardjo; Novike Dian Utami (2477 - 6165, 2021)
Project is something with constrains can affect the time or duration of the work, slope slides and building redesigns that have an impact on delays in project implementation. Delays that occur can result in the presence of less work and work items that cause work to experience delays and increase the total cost of implementing the project or it can be said that the project suffers a loss. In this case, good time and coast management needs, can be solved properly. This challenge of a project is main to achieve the goals project within the constraints which generally the scope, schedule and budget of the project. Many methods used in scheduling, for expected scheduling planning. This research to get a logical schedule by rescheduling in accordance that it is hoped no more delays. Analytic research need of data such as schedules and budgeting directly the required data to the relevant parts, evaluating the schedule, followed by a new schedules with Microsoft Excel, and finally perform cost calculations with a balanced budget system. The result of this research the rescheduling is 440 days with the total RAB after rescheduling is Rp. 41,286,988,000,-, equal to the total cost before rescheduling, because of the work added and less and carried out a balanced budget.